The Impact of Abdominal Drawing-in Maneuver and Tensor Fasciae Lataeiliotibial Band Self-stretching on Lumbopelvic Kinematics in Individuals With Lumbar Extension Rotation Syndrome - One-bin Lim; Oh-yun Kwon; Heon-seock Cynn; Chung-hwi Yi (Korean Research Society of Physical Therapy, 2024)
Background: The abdominal drawing-in maneuver (ADIM), a method of lumbar stabilization training, is an effective neuromuscular intervention for lumbar instability associated with low back pain (LBP). Objects: The purpose of this study was to compare the effect of a 2-week period of the ADIM and tensor fasciae latae-iliotibial band (TFL-ITB) self-stretching on lumbopelvic rotation angle, lumbopelvic rotation movement onset, TFL-ITB length, and pain intensity during active prone hip lateral rotation. Methods: Twenty-two subjects with lumbar extension rotation syndrome accompanying shortened TFL-ITB (16 males and 6 females) were recruited for this study. The subjects were instructed how to perform ADIM training or ADIM training plus TFL-ITB self-stretching program at home for a 2-week period. A 3-dimensional ultrasonic motion analysis system was used to measure the lumbopelvic rotation angle and lumbopelvic rotation movement onset. An independent t-test was used to determine between-group differences for each outcome measure (lumbopelvic rotation angle, lumbopelvic rotation movement onset, TFL-ITB length, and pain intensity). Results: The results showed that ADIM training plus TFL-ITB self-stretching decreased the lumbopelvic rotation angle, delayed the lumbopelvic rotation movement onset, and elongated the TFL-ITB significantly more than did ADIM training alone. Pain intensity was lower in the ADIM training plus TFL-ITB self-stretching group than the ADIM training alone group; however, the difference was not significant. Conclusion: ADIM training plus TFL-ITB self-stretching performed for a 2-week period at home may be an effective treatment for modifying lumbopelvic motion and reducing LBP.